2022
DOI: 10.3389/fneur.2022.690760
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gray and White Matter Volume Alterations in Patients With Post-Traumatic Anosmia: A Voxel-Based Morphometry Study

Abstract: ObjectiveTraumatic brain injury is one of the major causes of human olfactory dysfunction and leads to brain structure alterations, mainly in the cortical olfactory regions. Our study aimed to investigate volume changes in the gray matter (GM) and white matter (WM) in patients with post-traumatic anosmia and then to explore the relationship between GM volume and olfactory function.MethodsEthics committee approved prospective studies which included 22 patients with post-traumatic anosmia and 18 age- and gender-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…It should be noted, however, that loss of gray matter and functional imaging decrements in central olfaction-related brain structures has been associated with anosmia due to other causes. [61][62][63] Variables Associated with Long-Lasting Olfactory Dysfunction in COVID-19…”
Section: Causes Of Covid-19-related Smell Lossmentioning
confidence: 99%
“…It should be noted, however, that loss of gray matter and functional imaging decrements in central olfaction-related brain structures has been associated with anosmia due to other causes. [61][62][63] Variables Associated with Long-Lasting Olfactory Dysfunction in COVID-19…”
Section: Causes Of Covid-19-related Smell Lossmentioning
confidence: 99%
“…Considering that a decrease in the cortical gray matter was observed in subjects with anosmia [95,111], the cerebellum may be involved in OD in patients with pathologies primarily affecting the cerebellum. For example, it has been observed that patients with spinocerebellar ataxias exhibit OD [112,113].…”
Section: Cerebellummentioning
confidence: 99%